The effect of education on decreasing the prevalence and severity of neck and shoulder pain: a longitudinal study in Korean male adolescents - Koh, Min Jung (The Korean Society of Anesthesiologists, 2014)
BACKGROUND: Neck and shoulder pain is fairly common among adolescents in Korea and results in significant health problem. The aims of this prospective study was to identify the effects of education, in terms of recognition of this issue and posture correction, on prevalence and severity of neck and shoulder pain in Korean adolescents. METHODS: A prospective, observational cohort design was used. The 912 students from two academic high schools in the city of Seoul were eligible for the current study and 887 completed this study. After a baseline cross-sectional survey, students listened to a lecture about cervical health, focusing on good posture, habits, and stretching exercises to protect the spine, and were encouraged by their teachers to keep the appropriate position. And follow-ups were conducted 3 months later, to evaluate the effect of education. RESULTS: The prevalence of neck and shoulder pain was decreased 19.5% (from 82.5 to 66.4%). The baseline mean usual and worst numeric rating scale were 19.9/100 (95% CI, 18.1-21.7) and 31.2/100 (95% CI, 28.7-33.2), respectively. On the follow-up survey, the mean usual and worst numeric rating scale were decreased significantly by 24.1 and 21.7%, respectively, compared with baseline (P < 0.01). Of the 570 students reporting neck and shoulder pain, 16.4% responded that they had experienced improvement during the 3 months. CONCLUSIONS: Education; recognition of this issue and posture correction, for cervical health appeared to be effective in decreasing the prevalence and severity of neck and shoulder pain at a 3 month follow-up.